dexamethasone adjuvant therapy for refractory suppurative meningitis in children - Xu, Kang; Zhong, XiaoMei; Niu, QingJun (Journal of Medical Biochemistry, 2023)
Purpose: The aim of this study was to figure out the predictive value of inflammatory-linked factors on the efficacy of dexamethasone adjuvant therapy for refractory suppurative meningitis in children.Methods: Using regression analysis method, 38 children with refractory purulent meningitis, 40 children with purulent meningitis, and 40 healthy children who came to Qingtian County People's Hospital of Lishui City for physical examination during the same period were selected as the research objects, and assigned into the experimental, the control and the healthy groups. The inflammation-linked factors in the three groups were compared, and multivariate Logisitic regression was applied to analyze the predictive indicators and predictive efficacy of dexamethasone treatment in children with refractory suppurative meningitis.Results: CRP, TNF-α, IL-6, PCT and IL-1β were higher in the study group vs. the control and the healthy, and in the control vs. the healthy (P < 0.05). Multivariate Logisitic regression analysis clarified the predictors of the efficacy of dexamethasone treatment in children with refractory suppurative meningitis were CRP, TNF-α, IL-6, PCT, and IL-1β, which all had good predictive performance, and among which CRP and IL-1β had better predictive performance.Conclusion: Inflammatory-linked factors have a certain predictive value for the efficacy of dexamethasone adjuvant therapy for refractory suppurative meningitis in children.